Damage of concrete in uniaxial compression - An evaluation using ultrasonic method and optical microscopy - Kumar, S. Ashok; Santhanam, Manu (Journal of Structural Engineering, 2025)
This paper presents the damage assessment of normal and high strength concrete in short term uniaxial compressive loading using the ultrasonic method and optical microscopy. Ultrasonic signals, collected through concrete cubes loaded in compression up to varying fractions of the ultimate load, were analyzed for changes in wave velocity and amplitude. In addition, the frequency dependence of the signal was also studied for both types of concrete. The concrete structure preserved under load was also studied using optical microscopy, to validate the results obtained using the ultrasonic technique. Results revealed that the damage in normal concrete started at lower load levels (30 – 60%) compared to high strength concrete (more than 60%), and the failure was more gradual. The ultrasonic signal for normal strength concrete exhibited a strong frequency-dependence, while there was no such dependence in the case of high strength concrete – this indicates the homogenous nature of high strength concrete. The change in amplitude was a better measure of the deterioration inside the concrete (it showed a good correlation with the crack length development inside concrete that was measured from optical microscopy) as compared to the change in velocity, indicating that the wave velocity is not a good enough indicator of concrete damage.